Improving morphology and optoelectronic properties of ultra-wide bandgap perovskite via Cs tuning for clear solar cell and UV detection applications - Myo Zin Tun; Pimsuda Pansa-Ngat; Pipat Ruankham; Ko Ko Shin Thant; Sirawit Kamnoedmanee; Chaowaphat Seriwattanachai; Worawut Rueangsawang; Ratchadaporn Supruangnet; Hideki Nakajima; Pongsakorn Kanjanaboos (Scientific Reports, 2023)
Abstract With growing population, vertical spaces from skyscrapers are vast. Semi-transparent solar cells enable an effective pathway for vertical energy harvesting. With composition tunability, perovskite materials can be designed with different transparencies and colors. In this work, an ultra-high bandgap layered triple cation perovskite system was developed for the first time to meet the demand of clear optoelectronic applications; low dimensional triple cation perovskite thin films were fabricated using perovskite with the formula (PEA)2(CsxMA0.61-xFA0.39)39(Pb)40(Cl0.88-0.32xBr0.12+0.32x)121, 0 ≤ x ≤ 0.02 with DMSO as the appropriate solvent. The absorption edge of the material is around 410–430 nm, achieving great transparency to visible light. The structural, optical, and photovoltaic performances of the clear perovskite materials are explored with the variation of Cs contents via CsBr. The relation between thickness, transparency, and optoelectronic properties of the clear perovskite materials along with other physical properties were investigated. The highest photovoltaic conversion efficiency (PCE) of clear perovskite solar cells with 1.5% Cs was achieved to be 0.69% under xenon lamp irradiation at 100 mW/cm2 (1.5 mW/cm2 of UVA within 100 mW/cm2) and 5.24% under 365 nm UV irradiation at 2.4 mW/cm2. Photoresponsivity, external quantum efficiency (EQE), and detectivity were also determined for photodetector applications.